2020
DOI: 10.1002/hed.26221
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy, laryngoscopy, and esophagoscopy during the COVID‐19 pandemic

Abstract: Background: The United States now has the highest death toll due to COVID-19. Many otolaryngology procedures, including laryngoscopy, bronchoscopy, and esophagoscopy, place otolaryngologists at increased risk of coronavirus transmission due to close contact with respiratory droplets and aerosolization from the procedure. The aim of this study is to provide an overview of guidelines on how to perform these procedures during the coronavirus pandemic.Methods: Literature review was performed. Articles citing laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“… 5 Most studies universally recommend the following PPE: N95 mask or powered air-purifying respirators (PAPRs), gloves, gown, eye shield (or goggles), and cap. 1 , 5 , 11 , 15 , 16 It also has been suggested that the patients wear a mask covering the mouth during flexible laryngoscopy to reduce aerosolization from phonatory maneuvers and in case of coughing or sneezing. At this time, transoral rigid laryngoscopy and mirror laryngoscopy are discouraged unless flexible laryngoscopy cannot be performed due to the increased risk of gagging and coughing as well as the need for patients to phonate with the mouth uncovered to allow visualization of the larynx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Most studies universally recommend the following PPE: N95 mask or powered air-purifying respirators (PAPRs), gloves, gown, eye shield (or goggles), and cap. 1 , 5 , 11 , 15 , 16 It also has been suggested that the patients wear a mask covering the mouth during flexible laryngoscopy to reduce aerosolization from phonatory maneuvers and in case of coughing or sneezing. At this time, transoral rigid laryngoscopy and mirror laryngoscopy are discouraged unless flexible laryngoscopy cannot be performed due to the increased risk of gagging and coughing as well as the need for patients to phonate with the mouth uncovered to allow visualization of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests there is significant risk associated with elective surgery in seemingly asymptomatic patients who are infected with COVID-19. For this reason, many investigators have suggested preoperative COVID-19 testing, 15 , 26 , 27 , 28 although it is a subject of some debate. Some investigators advocate for a negative test within 48 hours followed by self-quarantine until the time of surgery, whereas others favor a negative test 48 hours from the time of surgery, and a point-of-care negative test on the day of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In deciding when instrumental assessment should be performed, swallowing experts should guarantee that the procedure avoids the following: COVID-19 infection of the examiner COVID-19 infection of the patient being examined as well as the incoming patients examined using the same instruments and/or in the same environment [ 7 ]. Instrumental assessment of swallowing (Videofluoroscopic Swallow Study, Fiberoptic Endoscopic Evaluation of Swallowing, Manometry) is performed only if appropriate cleaning and processing of the instruments according COVID-19 conditions can be guaranteed [ 8 10 ]. In both COVID+ve and COVID−ve patients, instrumental assessment of swallowing (Videofluoroscopic Swallow Study, Fiberoptic Endoscopic Evaluation of Swallowing, Manometry) is performed only if a potential life-threatening underlying disease is suspected, clinical assessment has not provided enough diagnostic information for effective treatment to be prescribed to the patients and the clinical situation does not allow the clinical decision to be postponed.…”
mentioning
confidence: 99%
“…Instrumental assessment of swallowing (Videofluoroscopic Swallow Study, Fiberoptic Endoscopic Evaluation of Swallowing, Manometry) is performed only if appropriate cleaning and processing of the instruments according COVID-19 conditions can be guaranteed [ 8 10 ].…”
mentioning
confidence: 99%